Analisis Pengaruh Parameter Permeabilitas Smear Zone Terhadap Penurunan Konsolidasi (Studi Kasus Di PLTU -Pekanbaru, Riau) - Ariza, Ariza; Satibi, Syawal; Fatnanta, Ferry (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Vertical drain is soil improvement method that aims to reduce the pore water pressure in soft ground so as to accelerate the consolidation process and time reduction in water-saturated soft soil. Tools vetikal precast drainage installation (Prefabricated Vertical Drain, PVD) is called a mandrel with a diameter of 60 to 70 cm2. Installation PVD candisturb the arrangement of soil around the walls of the mandrel, there by reducing the permeability of the soil that can slow down the process of consolidation. This study analyzes the disturb smear zone permebilityof consolidation settlement.This research showed the influence of smearzone permeability (kh/ks) very influence of consolidation settlement. Keys word :Vertical drain, Smear zonepermeability